Measuring and Reporting School and District Effectiveness - James L. Phelps (Educational Considerations, 2009)
The federal No Child Left Behind Act (NCLB), the 2001 reauthorization of Title I, requires states to assess students in grades three through eight in reading and mathematics, and students in three grades in science.
Keywords: Strategy; efficiency; school; mathematical; function; programs; models; students; measurement; equations; factors